The kingmaker's daughter [compact disc, unabridged] - Gregory, Philippa (Gregory, Philippa. Cousins' war, 2012)
The gripping story of the daughters of the man known as the "Kingmaker," Richard Neville, Earl of Warwick: the most powerful magnate in fifteenth-century England. Without a son and heir, he uses his daughters Anne and Isabel as pawns in his political games, and they grow up to be influential players in their own right.